Oral Spermidine Targets Brown Fat and Skeletal Muscle to Mitigate Diet‐Induced Obesity and Metabolic Disorders. Issue 19 (16th August 2021) - Wang, Di; Yin, Jilong; Zhou, Zixin; Tao, Yan; Jia, Yufeng; Jie, Haipeng; zhao, Jingyuan; Li, Ruiyu; Li, Yuan; Guo, Chun; Zhu, Faliang; Mao, Haiting; et al.
Abstract : Introduction: Obesity causes many life‐threatening diseases. It is important to develop effective approaches for obesity treatment. Oral supplementation with spermidine retards age‐related processes, but its influences on obesity and various metabolic tissues remain largely unknow. This study aims to investigate the effects of oral spermidine on brown adipose tissue (BAT) and skeletal muscle as well as its roles in counteracting obesity and metabolic disorders. Methods and Results: Spermidine is orally administrated into high‐fat diet (HFD)‐fed mice. The weight gain, insulin resistance, and hepatic steatosis are attenuated by oral spermidine in HFD‐fed mice, accompanied by an alleviation of white adipose tissue inflammation. Oral spermidine promotes BAT activation and metabolic adaptation of skeletal muscle in HFD‐fed mice, evidenced by UCP‐1 induction and CREB activation in both tissues. Notably, oral spermidine upregulates tyrosine hydroxylase in hypothalamus of HFD‐fed mice; spermidine treatment increases tyrosine hydroxylase expression and norepinephrine production in neurocytes, which leads to CREB activation and UCP‐1 induction in brown adipocytes and myotubes. Spermidine also directly promotes UCP‐1 and PGC‐1α expression in brown adipocytes and myotubes. Conclusion: Spermidine serves as an oral supplement to attenuate obesity and metabolic disorders through hypothalamus‐dependent or ‐independent BAT activation and skeletal muscle adaptation. Abstract : Spermidine, a natural polyamine residing in all organisms, can serve as an oral supplement to attenuate diet‐induced obesity, insulin resistance, and hepatic steatosis through hypothalamus‐dependent or ‐independent BAT activation and skeletal muscle adaptation. Brown fat, skeletal muscle, and hypothalamus are target tissues of oral spermidine. The activation of brown fat and metabolic adaptation of skeletal muscle can be directly mediated by spermidine, more importantly, be indirectly regulated by hypothalamus through spermidine‐induced tyrosine hydroxylase. CREB activation may contribute to tyrosine hydroxylase induction in neurocytes as well as PGC‐1α and UCP‐1 upregulation in brown adipocytes and myotubes.